Health of the elderly woman: a physiotherapy approach - Paiva, Rafaella; Balk, Rodrigo de Souza; Tier , Cenir Gonçalves (Disciplinarum Scientia | Saúde, 2024)
Objective: To evaluate the sociodemographic profile, functional capacity and cognitive level of elderly women. Method: Quantitative study, carried out with 15 women aged 60 years or over. Results: The sociodemographic results demonstrated that elderly women had a mean age of 70.73 ± 8.4 years, nine of whom (70%) were retired, six (40%) were married and five (35.7%) were illiterate. Among the comorbidities that most affect this population are hypertension (56%), heart failure (20%) and type II diabetes mellitus (16%). It was identified that twelve (80%) do not practice physical activities. In the data referring to the Mini Mental State Examination, six elderly women (42.9%) were identified with scores between 16 and 20 points, suggesting moderate cognitive loss. In the Timed Up and Go test, it was identified that five elderly women (33.3%) had impaired gait as they indicated a time greater than or equal to 30 seconds. Regarding the Tinetti test, (66.7%) were identified with scores between 19 and 24 points, categorizing a moderate risk of falls. Final considerations: It is concluded that elderly women in this age group present a reduction in functional and cognitive capacity, especially after the application of the tests, which is in line with other studies on this topic. However, the importance of the role of the physiotherapist in the Family Health Strategy was noted.